Pengaruh Kualitas Produk, Persepsi Harga, Dan Promosi Terhadap Keputusan Pembelian Kopi Janji Jiwa Di Cibubur Junction - Sinaga, Santo; Tarigan, Chatarina Yunita (Innovative: Journal Of Social Science Research, 2024)
Sustainable economic growth triggers increasingly fierce competition among coffee shop owners. In the midst of intense competition, companies are required to adapt to the latest trends in order to maintain and expand market share, encouraging business people to optimize performance. The purpose of this study was to determine the influence of product quality, price perception, and promotion on the decision to purchase soul promise coffee in Cibubur. In this study, the author used quantitative research methods by conducting a survey by distributing questionnaires of customers who shopped at Janji Jiwa coffee. Based on research findings: Product Quality (X1) has a positive and significant effect on the purchase decision of Janji Jiwa Cibubur Coffee. This price perception (X2) has a positive and significant influence on the purchase decision (Y) of Janji Jiwa Cibubur Coffee. Promotion (X3) has a positive and significant effect on the purchase decision (Y) of Janji Jiwa Cibubur Coffee. Product quality (X1), price perception, (X2) and promotion (X3) accounted for 57% of Janji jiwa Coffee purchases, while the other 43% were influenced by additional variables not addressed in this study.